Nazo, the Drosophila homolog of the NBIA-mutated protein-c19orf12, is required for triglyceride homeostasis. - Sreejith, P.; Lolo, S.; Patten, K.R.; Gunasinghe, M.; More, N.; Pallanck, L.J.; Bharadwaj, R. (PLoS Genetics, 2024)
Lipid dyshomeostasis has been implicated in a variety of diseases ranging from obesity to neurodegenerative disorders such as Neurodegeneration with Brain Iron Accumulation (NBIA). Here, we uncover the physiological role of Nazo, the Drosophila melanogaster homolog of the NBIA-mutated protein-c19orf12, whose function has been elusive. Ablation of Drosophila c19orf12 homologs leads to dysregulation of multiple lipid metabolism genes. nazo mutants exhibit markedly reduced gut lipid droplet and whole-body triglyceride contents. Consequently, they are sensitive to starvation and oxidative stress. Nazo is required for maintaining normal levels of Perilipin-2, an inhibitor of the lipase-Brummer. Concurrent knockdown of Brummer or overexpression of Perilipin-2 rescues the nazo phenotype, suggesting that this defect, at least in part, may arise from diminished Perilipin-2 on lipid droplets leading to aberrant Brummer-mediated lipolysis. Our findings potentially provide novel insights into the role of c19orf12 as a possible link between lipid dyshomeostasis and neurodegeneration, particularly in the context of NBIA.